The Role of Stone Culture from Pelvic and Bladder Urine in Predicting Urosepsis Among Patients Undergoing Percutaneous Nephrolithotomy in a Rural Center Catering to A Rural Population - Kanakasabapathy, Saravanan; Sethuraman, Thiripurasundari; Muthammal, Ramula; Arumugam, Mallika (Journal of Neonatal Surgery, 2025)
Background: Percutaneous nephrolithotomy (PCNL) has evolved significantly since its inception, becoming the preferred treatment for large and complex renal calculi. Despite advancements, postoperative infectious complications like urosepsis remain a major concern. Emerging evidence suggests that intraoperative cultures, particularly from pelvic urine and stone specimens, may predict urosepsis more reliably than preoperative bladder urine cultures. Objective: This study aimed to evaluate the predictive value of stone culture from pelvic and bladder urine in identifying the risk of urosepsis among patients undergoing PCNL in a rural healthcare setting. Secondary objectives included analyzing sex-based differences and the influence of comorbidities on urosepsis development. Materials and Methods: In this prospective observational cohort study, 100 patients undergoing PCNL were evaluated over 18 months. Bladder urine, pelvic urine, and stone fragments were cultured intraoperatively. Patients were monitored postoperatively for signs of urosepsis. Data on demographics, comorbidities, and stone characteristics were collected. Statistical analyses included Chi-square tests and logistic regression to determine predictors of urosepsis. Results: Among 100 patients (mean age 38.4 years; 50 males, 50 females), urosepsis occurred in 22% of those with positive bladder urine cultures and 50% with positive pelvic urine cultures, a statistically significant difference (p=0.0068). Middle-aged females with diabetes mellitus demonstrated the highest incidence of urosepsis in pelvic urine-positive cases. Logistic regression confirmed pelvic urine positivity as a strong independent predictor of postoperative urosepsis. Conclusion: Pelvic urine cultures provide superior predictive value for postoperative urosepsis compared to bladder urine cultures, particularly in diabetic, middle-aged female patients. Routine intraoperative collection and culture of pelvic urine during PCNL could enable early identification of high-risk individuals, guiding prompt prophylactic and therapeutic interventions to mitigate infectious complications in resource-limited rural healthcare settings.